2011
DOI: 10.1016/j.jbiomech.2011.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between vertical misfits and stresses transmitted to implants from metal frameworks

Abstract: An inappropriate prosthetic fit could cause stress over the interface implant/bone. The objective of this study was to compare stresses transmitted to implants from frameworks cast using different materials and to investigate a possible correlation between vertical misfits and these stresses. Fifteen one-piece cast frameworks simulating bars for fixed prosthesis in a model with five implants were fabricated and arranged into three different groups according to the material used for casting: CP Ti (commercially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
22

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 23 publications
3
27
0
22
Order By: Relevance
“…This is in disagreement with findings reported in the literature that state that discrepancies in the fit between a prosthesis and abutment can be overcome by the use of a bonding agent, thereby conferring greater stability to the set of components (17). It should be stressed that the abovementioned studies are laboratory studies (13,18) and bonding in such cases is performed under ideal, pre-established conditions. A number of factors can affect the bonding of prostheses on both teeth and implants, such as the preparation of the abutment, the taper of the abutment, surface area, surface roughness, type of cement and experience of the dentist (19).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This is in disagreement with findings reported in the literature that state that discrepancies in the fit between a prosthesis and abutment can be overcome by the use of a bonding agent, thereby conferring greater stability to the set of components (17). It should be stressed that the abovementioned studies are laboratory studies (13,18) and bonding in such cases is performed under ideal, pre-established conditions. A number of factors can affect the bonding of prostheses on both teeth and implants, such as the preparation of the abutment, the taper of the abutment, surface area, surface roughness, type of cement and experience of the dentist (19).…”
Section: Discussionmentioning
confidence: 69%
“…Forming sections and soldering structures can minimize discrepancies, but may not assure passive adaptation (10). Although there is no consensus regarding the degree of clinically-acceptable misfit (13), a fit which is not capable of causing any complication in the long term is defined as passive. It has been suggested that misfits smaller than 150µm are acceptable (8).…”
Section: Discussionmentioning
confidence: 99%
“…A passividade ou adaptação passiva é caracterizada pela existência de contato circunferencial simultâneo de toda a superfície de assentamento da prótese com todos os pilares de suporte, com apenas um dos parafusos distais apertados (Torres et al, 2011).…”
Section: Tomografias Computadorizadas -Tcsunclassified
“…Está claro na literatura que desajustes podem provocar complicações biomecânicas, como fratura de componentes do sistema, afrouxamento dos parafusos, reabsorções ósseas, alterações dos tecidos moles e até mesmo perda da osseointegração (Brånemark, 1983;Goll, 1991;Wee et al, 1999;Torres et al, 2011).…”
Section: Tomografias Computadorizadas -Tcsunclassified
See 1 more Smart Citation